Evaluation of Rubber Seed Meal in Broiler Diets - Radhamma Pillai A (Department of Poultry Sciences, College of Veterinary and Animal Sciences, 1978)
An experiment was conducted to study the utility of three levels of rubber seed meal in broiler diets. Two hundred, one-day old commercial broiler chicks were divided randomly in to eight groups of twenty five chicks each to form four treatments of two replicates each. The four dietary treatments contained 0, 15, 20 and 30 per cent RSM.